How to foster innovation in SMEs: evidence of the effectiveness of a project-based technology transfer approach - Frederic Hilkenmeier; Christian Fechtelpeter; Julian Decius (The Journal of Technology Transfer, 2021)
One of the main challenges in technology transfer is to actively involve small and medium-sized enterprises (SMEs)—which are most in need of and benefit the most from collaborative Research and Development (R&D) programs. This study presents a large-scale collaboration program which focuses on project-based technology transfer in SMEs with little to no prior experience in collaborative research projects. The core of this collaboration program is the temporary secondment of scientists from a Research and Technology Organization (RTO) into an SME to jointly work on a practical project objective—which is directly tailored to the demands of the SME. To evaluate the effectiveness of this approach in overcoming barriers related to finding the right collaboration partner, limited resources, and limited absorptive capabilities, we adopt the R&D Lifecycle Model as a theoretical framework. Our findings, using self-reported and objective data from 106 different projects in a structural equation model, highlight that most SMEs in the considered cluster environment not only successfully mastered a challenging topic in the context of industry 4.0 that immediately benefits the organization, but also engaged in new R&D projects to strengthen their scientific and technical human capital in the long term. Moreover, consistent with previous literature, we found that trust is the main driver within the R&D Lifecycle Model both in building capabilities and economic growth. Based on these insights, we consider a long and close secondment of scientists to SMEs as key for collaboration projects and discuss implications for research and future technology transfer approaches.
Keywords: 600; Small and medium-sized enterprises (SME); Technology transfer; R&D lifecycle model; Drivers; Barriers; Transfer projects